Influence of Color Temperature of White LED Diodes and Illumination Intensity on the Content of Photosynthetic Pigments in Chlorella vulgaris Algae Cells - Paweł Kondzior (Proceedings, 2019)
The purpose of this paper is to determine the influence of color temperature of Light Emitting Diode (LED) diodes and illumination intensity on the content of photosynthetic pigments of chlorophyll a, chlorophyll b and carotenoids in Chlorella vulgaris algae cells. Choosing the right color temperature and intensity of illumination can favorably affect the growth of algae. In particular, it can contribute to the efficiency of the photosynthesis process and the amount of produced biomass from Chlorella vulgaris algae. In the spectrophotometric studies, the highest content of chlorophyll a, chlorophyll b and carotenoids was found in cultures illuminated with very cold white light (8500 K) with an intensity of 500 μmol/m2s. The highest measured content of chlorophyll a (Chl a) pigments was 48.29 mg/L, Chl b pigment was 23.25 mg/L and carotenoids pigment was 12.65 mg/L; the smallest content of pigments for Chl a (11.48 mg/L), Chl b (4.69 mg/L) and carotenoids (3.03 mg/L) was found in the sample illuminated with warm white light (3200 K) with an intensity of 50 μmol/m2s. The highest amount of dry organic matter amounting to 2.0 g/L was found in a sample illuminated with warm white light (3200 K) with an intensity of 250 μmol/m2s, then 1.91 g dry organic mass (DOM)/L for very cold white light with an intensity of 250 μmol/m2s, and 1.48 g DOM/L for very cold white light with an intensity of 50 μmol/m2s. The obtained results show that a higher content of photosynthetic pigments does not directly affect the increase of the amount of dry organic matter.